2016
DOI: 10.1515/pjmpe-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

A standard Fricke dosimeter compared to an ionization chamber used for dosimetric characterization of 60Co photon beam

Abstract: The main objective of this study was to investigate the Fricke dosimeter water equivalent system for measurement of dosimetric parameters for photon beam. The parameters measured with the Fricke dosimeter were compared to those obtained with an ionization chamber. In this work characteristics for 60 Co γ-rays of field sizes ranging from 5 × 5 cm 2 to 20 × 20 cm 2 are reported. The measurements were carried out in the secondary standard dosimetry laboratory using a collimated 60 Co gamma source therapy unit. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Hence, no significant change of the Fricke response due to the magnetic field could be observed. Moussous and Medjadj (2016) have shown that output factors measured with Fricke detectors for field sizes between 5 × 5 cm 2 and 20 × 20 cm 2 in a 60 Co beam agree within 0.5% with ionization chamber measurements (WDIC70#141), when no magnetic field is applied. Here, we have measured output factors in the presence of magnetic field strengths between 0 T and 1.42 T using Fricke detectors.…”
Section: K Bmq and K Bq Factorsmentioning
confidence: 67%
See 1 more Smart Citation
“…Hence, no significant change of the Fricke response due to the magnetic field could be observed. Moussous and Medjadj (2016) have shown that output factors measured with Fricke detectors for field sizes between 5 × 5 cm 2 and 20 × 20 cm 2 in a 60 Co beam agree within 0.5% with ionization chamber measurements (WDIC70#141), when no magnetic field is applied. Here, we have measured output factors in the presence of magnetic field strengths between 0 T and 1.42 T using Fricke detectors.…”
Section: K Bmq and K Bq Factorsmentioning
confidence: 67%
“…The Fricke dosimetry method can be used as a primary standard for MeV electrons (Feist 1982, McEwen et al 2014 and the Federal Office of Metrology (METAS, Switzerland) has great experience with this application (Stucki et al 2003a, 2003b, Vörös et al 2012. Furthermore, Fricke detectors have been used as secondary standards for several different applications in photon and electron beams as well as in x-rays (Nahum and Greening 1978, Kuszpet et al 1982, Feist and Muller 1989, Palm and Mattsson 2002, Austerlitz et al 2006, Moussous et al 2011, deAlmeida et al 2014, Moussous and Medjadj 2016.…”
Section: Introductionmentioning
confidence: 99%